Developing a hierarchical type-2 fuzzy logic model to improve rapid evaluation of earthquake hazard safety of existing buildings. (December 2020) - Harirchian, Ehsan; Lahmer, Tom
Abstract: The demand for developing a rapid, reliable, and effective technique for prioritizing the buildings with high seismic vulnerability and assisting disaster mitigation in developing post-earthquake safety plans for highly vulnerable buildings, is always challenging for engineers. In this paper, a novel framework for earthquake vulnerability assessment of buildings via Rapid Visual Screening (RVS) is proposed using type-2 fuzzy. In the previous methods, investigators' subjective/qualitative decisions who performed the inspection are predominantly vague and uncertain. Due to crisp membership functions, the typical fuzzy set cannot cover all types of uncertainty. However, it can handle vagueness sufficiently besides being a quick and affordable method. A hierarchical structure is modeled by different interval type-2 fuzzy logic systems (IT2FLSs) to cover uncertainties in this approach. The effectiveness of the framework is demonstrated in two case studies in Turkey. The result of the analysis presents the robust efficiency of the proposed method. However, this work's scope was only reinforced concrete buildings, but it is easy to adapt to different types of buildings, seismic zones, and countries.